1988
DOI: 10.1126/science.2969618
|View full text |Cite
|
Sign up to set email alerts
|

cDNA Expression Cloning of the IL-1 Receptor, a Member of the Immunoglobulin Superfamily

Abstract: Interleukin-1 alpha and -1 beta (IL-1 alpha and IL-1 beta) are cytokines that participate in the regulation of immune responses, inflammatory reactions, and hematopoiesis. A direct expression strategy was used to clone the receptor for IL-1 from mouse T cells. The product of the cloned complementary DNA binds both IL-1 alpha and IL-1 beta in a manner indistinguishable from that of the native T cell IL-1 receptor. The extracellular, IL-1 binding portion of the receptor is 319 amino acids in length and is compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
317
1
12

Year Published

1989
1989
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 854 publications
(333 citation statements)
references
References 38 publications
3
317
1
12
Order By: Relevance
“…EL-4 6.1 Cl0 express type I IL-l receptor that is structurally different from the type II IL-1 receptor expressed on 7OZ/3 cells [26,27]. Neither type I nor type II IL-1 receptor is a tyrosine kinase [26,27], but as in the case of the IL-2 receptor ut the surface immunoglobulin our study shows that IL-1 receptors can nonetheless stimulate protein tyrosine kinase activity. It remains to be determined whether or not the same protein tyrosine kinase(s) are activated by IL-la in 7CW3 and EL4 6.1 Cl0 cells.…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…EL-4 6.1 Cl0 express type I IL-l receptor that is structurally different from the type II IL-1 receptor expressed on 7OZ/3 cells [26,27]. Neither type I nor type II IL-1 receptor is a tyrosine kinase [26,27], but as in the case of the IL-2 receptor ut the surface immunoglobulin our study shows that IL-1 receptors can nonetheless stimulate protein tyrosine kinase activity. It remains to be determined whether or not the same protein tyrosine kinase(s) are activated by IL-la in 7CW3 and EL4 6.1 Cl0 cells.…”
Section: Resultsmentioning
confidence: 53%
“…Some receptors, like the insulin, PDGF or EGF receptors are tyrosine kinases, while others like the IL-2 receptor or the surface immunoglobulin increase tyrosine phosphorylation even though they are not tyrosine kinases [24,25]. EL-4 6.1 Cl0 express type I IL-l receptor that is structurally different from the type II IL-1 receptor expressed on 7OZ/3 cells [26,27]. Neither type I nor type II IL-1 receptor is a tyrosine kinase [26,27], but as in the case of the IL-2 receptor ut the surface immunoglobulin our study shows that IL-1 receptors can nonetheless stimulate protein tyrosine kinase activity.…”
Section: Resultsmentioning
confidence: 99%
“…5 The two forms of IL-1, IL-1␣ and IL-1␤, together with the structurally related antagonist (IL-1ra) are all distinct gene products, but bind to a common receptor composed of two type I integral membrane proteins (IL1RI and IL1RacP). 6,7 The interleukin 1 type 1 receptor (IL1-RI) (MIM 147810) is the signal-transducing receptor for IL-1. 8 The receptor is found on most cells, including T lymphocytes and beta cells.…”
Section: Introductionmentioning
confidence: 99%
“…Although they are only poorly homologous in their primary sequences, the two IL-1 isoforms have been reported to bind a common class of receptors on a variety of cell types including T and B cells [2] and fibroblasts [3]. The sequence of a cDNA encoding an 80 kDa polypeptide responsible for the binding of IL-1 on routine EL4-6.1 thymoma has been recently reported [4]. In the same study, COS cells expressing this recombinant IL-1R polypeptide have been shown to bind IL-lo< and IL-IB with markedly different affinities [4].…”
Section: Introductionmentioning
confidence: 99%